Effectiveness of Guided Inquiry Learning Model Using Scientific Approach to Improve Students' Critical Thinking Skills - Setiawan, Bayu Budi; Supardi, Zainul Arifin Imam (Jurnal Penelitian Pendidikan Fisika, 2021)
This research aims to improve students' critical thinking skills using guided inquiry models that was completed by scientific approach in momentum and impulses subjects. This research used pre-experimental method using one group pre-test and post-test design. The research was conducted at SMAN 3 Sidoarjo using one experimental class research design, namely class X MIA 3. The research variables used in the research were guided inquiry models using scientific approach as a manipulation variable, while the ability to think critically and the achievement learning as a respond variable. This research used homogeneity testing techniques to determine the homogeneity of data, normality test to know the category of normal distribution, t-pair test to compare between pre-test and post-test values, analysis of n-gain to find the improvement of student's critical thinking skills, and quantitative and descriptive technique to describe the implementation of learning using guided inquiry models. This research concluded that learning using guided inquiry models had improved the student's critical thinking skills in high categories and its implementation is very good categories.